Visual Discourse Analysis of Zohran Mamdani's Campaign in New York: Urban Aesthetics and Shifts in Political Representation - Kholis, Achmad Nur; Nidya Kinasih, Afusa (Faculty Of Arts and Design Sebelas Maret University, 2025)
Contemporary political communication shows a significant shift towards the dominance of visual culture, especially in the context of political campaigns in metropolitan areas. Visuals no longer function as supporting elements, but as the main medium in shaping images, social relations, and political discourse. This study aims to analyze the visual strategies of Zohran Mamdani's campaign in the 2025 New York City mayoral election using the Grammar of Visual Design framework. This study uses a descriptive qualitative approach with visual analysis methods on campaign materials in the form of posters, digital content, and graphic designs published through the campaign's official online media. The results show that Mamdani's campaign shifts the center of political meaning from the dominance of the candidate's figure to a collective representation based on the city's identity and urban experience. Representational analysis shows that the city is positioned as the main political subject, while the candidate's figure is subordinated in a broader visual system. In the interactive and compositional dimensions, an egalitarian relationship between candidates and voters is built through non-authoritative gazenon, equal social distance, and the dominance of design structures such as color, typography, and layout. These findings show that visual design operates as an active political actor in shaping urban political discourse. This research contributes to the study of Visual Communication Design by positioning political campaign design as a cultural practice that produces meaning, social relations, and political ideology. Keywords: visual political communication, campaign design, Grammar of Visual Design, urban identity, Zohran Mamdani